Coloration of different textile fibers using glycerol oxides. Issue 20 (December 2016) - Ohe, Takeru; Nakai, Takeo; Yoshimura, Yurika
We have investigated new applications of the Maillard reaction in textile industries as an alternative to conventional dyeing methods. Our previous paper indicated that only textile fibers having amino groups, such as wool, silk, and nylon fibers, were colored by chemical reactions with reducing sugars, such asd -glucose andd -xylose, but these coloration reactions were very slow compared with conventional dyeing methods. Recently, we obtained important results from our preliminary studies that trioses, such as glyceraldehyde, imparted deeper coloration to the textile fibers than other reducing sugars. However, these trioses are too expensive to be used as raw colorant materials for the textile industry. In this paper, the coloration reactions of the textile fibers having amino groups with glycerol oxides, which were obtained from low-cost glycerol by the Fenton reaction, were investigated. Interestingly, the obtained fibers were observed to be more deeply colored by the glycerol oxides than the reducing sugars mentioned above, including glyceraldehyde. Furthermore, when the wool fibers were heated in neutral or basic solutions containing glycerol oxides, the color of the fibers quickly became dark brown or almost black.